Processing effects on safety and quality of foods (CRC Press, 2010)
Thermal processing is known to effectively control microbial populations in food, but the procedure also has a downside―it can break down the biochemical composition of foods, resulting in a marked loss of sensory and nutritional quality. Processing Effects on Safety and Quality of Foods delineates three decades of advances made in processing techniques that produce microbiologically safe foods, while maintaining their sensory and nutritive properties.